Comparison of Fracture Strength Between Veneered and Full-Contour Zirconia Restorations (Without Surface Treatment) With PMF - Hosam Elarabi; Abdulhakim Omar; Nasser Allaian; Bahaddin Emhmed; Salah Ali (AlQalam Journal of Medical and Applied Sciences, 2025)
The purpose of this in vitro study is to investigate the fracture of zirconia in the posterior region and to compare between fracture strength of zirconia crowns and porcelain fused to metal restorations. Twenty human maxillary premolars were prepared for two zirconia all-ceramic crown systems with the following preparation criteria: 6-degree axial taper, 1-mm shoulder finish line, 2-mm occlusal reduction, and occluso-gingival height of 5 mm. All specimens were divided into two groups (n=10) for each ceramic material. In the first group, all prepared premolars were restored by full contour zirconia crowns (mad/mam), while in the second group, all teeth were restored by veneered zirconia crowns. The cores were directly fabricated (Vita In-Ceram blocks) by MAD/MAM and built up with ceramic. All specimens were loaded in a universal testing machine with the compressive load (n) applied along the axis of the specimen. Fracture load was recorded for each specimen. The Kruskal-Wallis test was used first and followed by the Mann-Whitney test. The fracture strength records a highly significant difference between VZ and FZ (p=0 for both tests), irrespective of the type of surface treatment. Contrarily, both tests proved that the surface treatment has no significant effect on fracture resistance, irrespective of the type of material (p=0.72 for median test and p=0.27 for Mann-Whitney test). The fracture strength of zirconia is high in the posterior region, and full-contour zirconia showed higher fracture strength than veneered zirconia crowns and porcelain fused to metal restorations.